Environmental Parameters and Substrate Type Drive Microeukaryotic Community Structure During Short-Term Experimental Colonization in Subtropical Eutrophic Freshwaters - Zhu, Changyu; Bass, David; Wang, Yutao; Shen, Zhuo; Song, Weibo; Yi, Zhenzhen (Frontiers in Microbiology, 2020)
Microeukaryotes are key components of aquatic ecosystems and play crucial roles in aquatic food webs. However, influencing factors and potential assembly mechanisms for microeukaryotic community on biofilms are rarely studied. Here, those of microeukaryotic biofilms in subtropical eutrophic freshwaters were investigated for the first time based on 2,585 OTUs from 41 samples, across different environmental conditions and substrate types. Following conclusions were drawn: (1) Environmental parameters were more important than substrate types in structuring microeukaryotic community of biofilms in subtropical eutrophic freshwaters. (2) In the fluctuating river there was a higher diversity of OTUs and less predictability of community composition than in the stable lake. Sessile species were more likely to be enriched on smooth surfaces of glass slides, while both free-swimming and attached organisms occurred within holes inside PFUs (Polyurethane Foam Units). (3) Both species sorting and neutral process were mechanisms for assembly of microeukaryotic biofilms, but their importance varied depending on different habitats and substrates. (4) The effect of species sorting was slightly higher than the neutral process in river biofilms due to stronger environmental filtering. Species sorting was a stronger force structuring communities on glass slides than PFUs with more niche availability. Our study sheds light on assembly mechanisms for microeukaryotic community on different habitat and substrate types, showing that the resulting communities are determined by both sets of variables, in this case primarily habitat type. The balance of neutral process and species sorting differed between habitats, but the high alpha diversity of microeukaryotes in both led to similar sets of lifecycle traits being selected for in each case.